EDITORIAL - Vongurai, Rawin (Scholar: Human Sciences, 2025)
The Scholar: Human Sciences, a journal encompassing the fields of humanities and social sciences, has earned acclaim in the Thailand Citation Index (TCI) as a prominent publication since 2015. It currently holds the esteemed TCI: TIER1 classification. We take great pride in presenting the latest issue, which features a collection of manuscripts that have undergone rigorous evaluation. Each submission has been meticulously reviewed through a blinded review process by three specialized reviewers from different institutions, both internal and external to the authors. This peer-reviewed accreditation ensures the scholarly quality and integrity of the published articles. This issue covers thirty articles. The first article titled “Factors Impacting Teachers' Happiness on Higher Education in Zhanjiang University of Science and Technology, China” explored the correlation between factors such as teachers' income, teachers' wealth, teachers' health, sense of gain, sense of fairness, and teachers' happiness. The second article titled “Assessing Posttraumatic-Stress Disorder Symptoms among Former Rebels: Basis for Mental Health Care Intervention” investigated the socio-demographic characteristics and psychosocial health profile of the former rebels in terms of posttraumatic-stress symptomatology. The third article titled “Exploring the Impact of Mobile Apps on English Vocabulary Learning Intentions Among Gen X Adults Learners in Chengdu, China” investigated the impact of Gen X users in Chengdu, China, on their English learning behavior intention by using the most popular English word learning Applications in China among system quality, information quality, service quality, perceived usefulness, attitude, technology characteristics, task characteristics, task-technology fit and behavior intention. The fourth article titled “Influencing Factors of Students’ Use of New Media Teaching Classes on the Learning Attitude and Learning Satisfaction in Guangdong, China” explored the factors that influence the satisfaction and attitude of international trade students in Guangdong Province. The fifth articled titled “Determining Factors of Financial Performance and Firm Value: A Case Study of a Rice Company in Chengdu, China” explored the factors affecting the financial performance and firm value of a rice company in Chengdu City, China. The sixth article titled “A Study on the Influencing Factors of Students' Academic Performance in Guangdong Private University, China” examined the factors, which include school culture, teacher commitment, teacher emotional intelligence, teacher collective efficacy, and teacher instructional leadership, that improve students’ academic performance in a private university in Guangdong. The seventh article titled “A Qualitative Study in Using the Curriculum Cycle Model and Genre Theory to Improve Students’ Business Negotiation Writing Performance in Chinese University Contexts” investigated the effectiveness of integrating a curriculum cycle model and genre theory to enhance Chinese university students' proficiency in business English negotiation writing. The eighth article titled “Turning Trash into Treasure: Unveiling Public Approval and Government Energy Policies in Thailand's Waste-to-Energy Evolution” aimed to examine the significant impact of trust in government, perceived risk, perceived benefits, place attachment, government energy policies, public acceptance on waste-to-energy development. The ninth article titled “Driving Factors of Students’ Achievement: A Case Study of a Private University in Zhanjiang, China” investigated the impact of four independent variables (teacher commitment, emotional intelligence, professional development, and professional community) on the dependent variable (student achievement). The tenth article titled “Students’ Satisfaction with Blended Learning in a Public College in Chengdu, China” explored the impact of five independent variables: teaching presence, system quality, information quality, perceived usefulness, and self-efficacy. The eleventh article titled “Factors Impacting E-shopping Intention Among Undergraduate Students in a Public University in China” explored the impact of college undergraduate students' e-shopping usefulness, attitude, and intention in Guangxi University of Science and Technology (GXUST), China. The twelfth article titled “Factors Influencing Attitude and Purchased Intention Toward Electric Vehicles of Chinese Consumers in Shenzhen, China” determined the factors influencing Chinese consumers' attitudes and purchase intentions toward electric vehicles in Shenzhen, China. The thirteenth article titled “Examining Behavioral Intention and Use Behavior in Online Learning Among Students of Vocal Language and Art College in Chengdu, China” explored the factors affecting students' behavioral intention and use behavior in the context of online learning at a private university specializing in vocal language and art college in Chengdu, China. The fourteenth article titled “The Influencing Factors of Perceived Value, Satisfaction, And Intention to Reuse Online Shopping in College Students at A Public University in Hangzhou, China” determined the factors influencing perceived value, satisfaction, and intention to reuse online shopping among college students at a public university in Hangzhou, China. The fifteenth article titled “Influencing Factors of Online Learning Courses Satisfaction in Art Major: A Case Study of Chongqing, China” employed a mixed-methods approach to investigate online learning satisfaction of students in art education. The sixteenth article titled “Determinants of Students’ Learning Satisfaction in E-learning English Class in Chongqing University, China” attempted to evaluate the critical factors that have a major impact on students learning satisfaction in an online English course. The seventeenth article titled “Determinants of Student Engagement in Nursing Vocational Education in Shanghai, China” studied the influence of seven independent variables (Analytical Skills, Experience Quality and Supportive Study Climate) on one dependent variable (Student Engagement). The eighteenth article titled “An Analysis of Factors Influencing College Students' Satisfaction With E-learning: A Case Study of Guangdong City Technician College in Guangdong, China” investigated the influence of six independent variables (System Quality, Perceived Usefulness, Perceived Ease of Use, and Confirmation) on the dependent variable (Satisfaction) with e-learning. The nineteenth article titled “Factors Affecting Consumers’ Conformity, Trust, and Purchase Intention in Live Streaming Shopping in Hangzhou, China” examined a causal relationship among professionalism, price discounts, immersion, parasocial interaction, social presence, consumer conformity, trust, purchase intention. The twentieth article titled “Drivers Influencing Consumers' Online Shopping Intentions in Chengdu, China” investigated the key factors influencing online shopping behavior among people in Chengdu, China. The twenty-first article titled “Factors Impacting Student Learning Performance in Blending Learning in a Graphic Design Course: A Case Study of Private University in Liaoning Province, China” investigated the impact of five independent variables (learning anxiety, learning attitude, learning motivation, social media usage, and feedback) on one dependent variable (student learning performance in blended learning). The twenty-second article titled “Factors Impacting Students’ Confirmation, Learning Engagement, Satisfaction, and Continuous Intention of Online English Learning in Vocational Colleges in Hangzhou, China” examined first-year and second-year students’ satisfaction and continuous intention toward online English learning in Hangzhou, China. The twenty-third article titled “Factors Influencing Undergraduate Students' Attitude and Behavioral Intention to Use Library social media in Sichuan, China” aimed to examine the factors influencing undergraduate students' behavioral intentions to utilize library social media services in China, focusing on Academic Library WeChat Official Accounts (ALWCOA). The twenty-fourth article titled “Improving Student Satisfaction in The Learning Chinese as a Foreign Language in Dhaka, Bangladesh” explored the impact of five dependent variables (perceived teaching quality, emotional support, student-lecturer attachment, service quality, reputation, and physical environment) on the independent variable of student satisfaction. The twenty-fifth article titled “Factors Influencing University Students’ User Satisfaction and Continuous Intention to Use Short Video Apps for Learning in Beijing, China” aimed to research the factors influencing University Students’ user satisfaction and continuous intention to Use Short Video App for Learning in Beijing, China. The twenty-sixth article titled “Factors Impacting Vocational Education' Satisfaction, Learning Engagement, and Continuance Intention of MOOCs” aimed to enhance vocational school students' satisfaction, learning engagement, and intention to use MOOCs in Hangzhou, China. The twenty-seventh article titled “Determinants of Students’ Blended Learning Engagement and Satisfaction Toward Students at Public Colleges in Hangzhou, China” posited causal relationships between teacher structured approach, student self-efficacy, learning assessment, interpersonal skills, perceived usefulness, student learning engagement, and student satisfaction. The twenty-eighth article titled “Exploring the Drivers of Entrepreneurial Intentions and Behaviors Among Higher Vocational Students in Xuzhou, China” aimed to increase entrepreneurial intentions and promote entrepreneurial behavior among higher vocational students. The twenty-ninth article titled “Exploring the Drivers of Undergraduates’ Perceived Usefulness and Intention to Adopt Cloud Computing: A Study in Chengdu, China” investigated the elements that affect the perceived usefulness and intention to use cloud computing among undergraduates in Chengdu, China. The thirtieth article titled “Key Factors Shaping Satisfaction and Continued Use of MOOCs Among Computer Science Majors: Insights from Sichuan, China” determined how satisfied undergraduate computer science students are with using Massive Open Online Course (MOOCs) for learning at a science and technology university in Sichuan, China.